Mothers Who Kill Their Children: Literature Review and Reflections for Social Work Practice. Issue 5 (11th November 2022) - Davies, Andrew
Abstract : The author worked within a Children Services Social Work department at the time of a high profile case involving the homicide of two children by their mother and father. Drawing on this experience, the article seeks to explore why mothers are involved in killing their children through reviewing the literature around how maternal filicides are classified and any complicating factors before finally considering reflections for Social Work practice. This article concludes that the reasons why a mother kills their child are a complex result of social and psychological factors. Social Workers and other professionals working with children can learn from the specific types of maternal filicides that can occur and also what factors may influence such events taking place.